Deixis, Historical Memory and the Contradictions of Postcolonial Freedom in Oloruntoba-Oju’s Losses - Theophilus Okunlola (Nordic Journal of African Studies, 2021)
This paper studies Taiwo Oloruntoba-Oju’s Losses (Poems) (1998). It situates the collection within the tradition of works written against the repressive military regime in Nigeria, and in Africa in general, pointing out the centrality of historical memory as used in the creation of a poetics of lamentation, resistance, and denunciation. In studying the prevalence of memory in the poems, I employ deixis as a paradigm to track the social environment which the poet creates; the person, place, and time of discourse are directly related to the dominant issue of social suppression, which is painfully remembered and represented in the poems. While the most common research approaches in memory studies have adopted models from anthropology, literature, archaeology, sociology, and popular culture, this work argues that a linguistic approach, particularly pragmatics, is equally suitable because of the way it situates meanings within specific social and ideological contexts. In employing this linguistic approach, this work examines how memory becomes a tool for protest and resistance against the dictatorial regimes in Nigeria. More precisely, it foregrounds the notion of freedom in postcolonial states as being intricately tied to the burden of remembering the past and learning from its pitfalls in order to build a better future.